Graph data mining-based community clustering for gender-biased community detection of social media - Dev, Sanjoy; Tabassum, Maliha; Khan, Mohammad Rahat; Hoque, Maliha Bushra; Fatema, Basharat (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.